MEMBANGUN SPIRITUALITAS BERDASARKAN SURAT 1 TIMOTIUS 4:12 - Manase Gulo (Manna Rafflesia, 2014)
Life in this day and age is shaped by various elements that influence one another, so that each person becomes a unique person. Influence comes from family background, social culture, economic factors and bad habits, depending on the environment in which a person lives. Paul wanted to talk to them as spiritual people, but he found that they were still "babies" he could only give them milk, because they were still not ready to receive hard food (1 Cor 3: 1-3). Spirituality is an important part of human life, with a healthy spirituality humans will live life well. Spiritualiats are an important force in sustaining our lives, through good spirituality humans can deal with bad conditions. Through the advice of the Apostle Paul to Timothy we get important principles to build spirituality.